The calcimimetic R-568 retards uremia-enhanced vascular calcification and atherosclerosis in apolipoprotein E deficient (apoE-/-) mice - Ivanovski, Ognen; Nikolov, Igor G; Joki, Nobuhiko; Caudrillier, Axelle; Phan, Olivier; Mentaverri, Romuald; Maizel, Julien; Hamada, Yasuhiro; Nguyen-Khoa, Thao; Fukagawa, Masafumi; Kamel, Said; Lacour, Bernard; et al. (Elsevier BV, 2009)
Secondary hyperparathyroidism of chronic kidney disease promotes vascular calcification. Calcimimetics reduce serum parathyroid hormone, calcium (Ca), and phosphorus by calcium-sensing receptor (CaR) activation. Here we examined possible effects of the calcimimetic R-568 (R-568) on the progression of aortic calcification and atherosclerosis in apoE(-/-) mice with chronic renal failure (CRF) and the potential implication of aortic smooth muscle cell CaR.